In-house provisioning and South African public procurement law - Quinot, G. (Faculty of Law, University of the Free State, 2014)
English: Public procurement is a highly regulated aspect of state administration and an area in which litigation is frequent in South Africa. As Nugent JA noted in South African Post Office v De Lacy:1 “Cases concerning tenders in the public sphere are coming before the courts with disturbing frequency.” It is thus surprising that the question of in-house provisioning was only pertinently raised in South African courts in the matter of Cash Paymaster Services (Pty) Ltd v The Chief Executive Officer of The South African Social Security Agency,2 which commenced in the High Court towards the end of 2009, winding its way through the judicial system to a Constitutional Court order in mid-2011. However, more surprising and somewhat disappointing, none of these courts used this opportunity to squarely deal with the question so that it still remains largely an unresolved one in South African law. In this contribution, I assess the judgments in the Cash Paymaster Services case and discuss some of the pertinent issues that will have to be addressed when the next opportunity arises to deal with in-house provisioning.
Keywords: Government purchasing; Tenders